2017
DOI: 10.3892/or.2017.5753
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 inhibits growth of gastric cancer by inhibiting JAK2/STAT3 pathway

Abstract: SIRT6, a member of NAD positivity-dependent class III deacetylase sirtuin family, played versatile roles in human cancers. However, the expression and biological function of SIRT6 in gastric cancer (GC) remain to be investigated. In this study, we found that SIRT6 expression level was decreased in gastric cancer tissues and cell lines. Decreased SIRT6 expression was associated with unfavorable clinical parameters including tumor differentiation, tumor size and TNM stage. Importantly, decreased level of SIRT6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…Previous study has revealed that the JAK2/STAT3 signaling pathway is highly activated in colon cancer, and contributes to proliferation, migration, invasion, cell cycle progression and angiogenesis ( 21 - 24 ). The association between SIRT6 and JAK2/STAT3 has been confirmed in other cancers; however, to the best of our knowledge, it has not been reported in colon cancer ( 20 , 25 ). Therefore, the present study aimed to determine the effects of SIRT6 overexpression on the JAK2/STAT3 signaling pathway.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous study has revealed that the JAK2/STAT3 signaling pathway is highly activated in colon cancer, and contributes to proliferation, migration, invasion, cell cycle progression and angiogenesis ( 21 - 24 ). The association between SIRT6 and JAK2/STAT3 has been confirmed in other cancers; however, to the best of our knowledge, it has not been reported in colon cancer ( 20 , 25 ). Therefore, the present study aimed to determine the effects of SIRT6 overexpression on the JAK2/STAT3 signaling pathway.…”
Section: Resultsmentioning
confidence: 61%
“…SIRT6 acts as a cancer suppressor gene in pancreatic cancer by controlling Lin-28 homolog B ( 30 ), and promotes cytokine production and migration in pancreatic cancer cells by regulating Ca 2+ responses ( 31 ). Decreased expression of SIRT6 promotes tumor cell growth and is closely correlated with the poor prognosis of ovarian cancer, gastric cancer and glioma ( 20 , 25 , 32 ). In non-small cell lung cancer, SIRT6 can suppress cell proliferation via the inhibition of Twist1, and astragaloside IV can sensitize non-small cell lung cancer cells to gefitinib by upregulating SIRT6 ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 miR-148a can act as a tumor suppressor by inhibiting CCK-BR and inactivating STAT3 in GC. The miR-93-5p/IFNAR1 axis can promote GC metastasis by stimulating the STAT3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our study, SIRT6 overexpression-induced apoptosis, activated caspase-9 and caspase-3 in human gastric cancer cells, resulting in cell cycle arrest, induced cellular apoptosis through inactivation of JAK2/STAT3 signaling, and by downregulation of cyclin D1 and Bcl2. 28 Apoptosis was also observed in A549 non-small-cell lung cancer cells, 29 mouse embryonic fibroblasts, 30 and hepatocellular carcinoma, 10 with downregulation of cell survival proteins (JAK2/STAT3 and Bcl-2), and upregulation of pro-apoptotic proteins (p53 and E2F-1, Bid and bax). However, several reports implicate a suppressive role of SIRT6 in cellular apoptosis, which is inconsistent with the results of our study.…”
Section: Discussionmentioning
confidence: 95%